EFFICACY OF Hirsutella thompsonii Fisher WITH CHEMICAL ACARICIDES AGAINST Tetranychus urticae Koch. ON OKRA UNDER FIELD CONDITIONS (Applied Biological Research, 2026)
Okra cultivated during summer season is highly susceptible to mite infestation. These mites thrive in hot and dry conditions, leading to severe damage to the crop. Therefore, proper monitoring and timely management practices are essential to control mite infestation in summer-grown okra. A field experiment was conducted at College Farm, NAU, Navsari (India) from February to May 2021 in a randomized block design with eight treatments including a control so as to evaluate the efficacy of various acaricides against the spotted spider mite, Tetranychus urticae infesting okra in field condition. The results revealed that all the test acaricides were significantly superior over untreated control in checking the spider mite population. Among the acaricides, fenazaquin 10 EC @ 2.5 mL L-1 was most effective and gave 78.4% control of spider mite, which was at par with spiromesifen 240 SC @ 0.8 mL L-1(76.73%) and propargite 57 EC @ 2 mL L-1(76.62%), which were best, with higher mite mortality in okra. Fenpyroximate 5 EC @ 1 mL L-1(62.22%) and diafenthiuron 50 WP @ 1 mL L-1(51.24%) were positioned in the next order, while the lowest mite mortality was observed in hexythiazox 5.45 EC @ 1 mL L-1(39.72%) and Hirsutella thompsonii @ 4 g mL-1(25.69%).
Keywords: Acaricides, bio-efficacy, Hirsutella thompsonii, okra, tetranychus urticae